The Effect of The Science Web Module Integrated on Batik’s Local Potential Towards Students’ Critical Thinking and Problem Solving (Thinking Skill) - Agnesi Sekarsari Putri; Nurfina Aznam (Journal of Science Learning, 2019)
The 21st-century learning paradigm requires teachers to provide teaching materials that can develop students' thinking skills. This research aims to determine the effect of the web module science integrated local batik potential toward the thinking ability of seventh-grade students of junior high school. The research method used was quasi-experimental design with a posttest-only design. The instrument used is about thinking skill. The data analysis technique is a Kruskal Wallis test and Effect Size. The results of the research showed that there were differences in students' thinking skill between the experimental class and the control class, as indicated by the Kruskal Wallis test, gives significant results. Web science module integrated with local batik potential has a significant influence on students' thinking skill as indicated by Cohen's effect size score of 0.8. The results of this research can be used to provide insights to science teachers create innovative learning materials to make students more interested in learning science and practicing thinking skills of students.